Origin and evolution of dengue virus type 3 in Brazil. - Josélio Maria Galvão de Araújo; Gonzalo Bello; Hector Romero; Rita Maria Ribeiro Nogueira (PLoS Neglected Tropical Diseases, 2012)
The incidence of dengue fever and dengue hemorrhagic fever in Brazil experienced a significant increase since the emergence of dengue virus type-3 (DENV-3) at the early 2000s. Despite the major public health concerns, there have been very few studies of the molecular epidemiology and time-scale of this DENV lineage in Brazil. In this study, we investigated the origin and dispersion dynamics of DENV-3 genotype III in Brazil by examining a large number (n=107) of E gene sequences sampled between 2001 and 2009 from diverse Brazilian regions. These Brazilian sequences were combined with 457 DENV-3 genotype III E gene sequences from 29 countries around the world. Our phylogenetic analysis reveals that there have been at least four introductions of the DENV-3 genotype III in Brazil, as signified by the presence of four phylogenetically distinct lineages. Three lineages (BR-I, BR-II, and BR-III) were probably imported from the Lesser Antilles (Caribbean), while the fourth one (BR-IV) was probably introduced from Colombia or Venezuela. While lineages BR-I and BR-II succeeded in getting established and disseminated in Brazil and other countries from the Southern Cone, lineages BR-III and BR-IV were only detected in one single individual each from the North region. The phylogeographic analysis indicates that DENV-3 lineages BR-I and BR-II were most likely introduced into Brazil through the Southeast and North regions around 1999 (95% HPD: 1998-2000) and 2001 (95% HPD: 2000-2002), respectively. These findings show that importation of DENV-3 lineages from the Caribbean islands into Brazil seems to be relatively frequent. Our study further suggests that the North and Southeast Brazilian regions were the most important hubs of introduction and spread of DENV-3 lineages and deserve an intense epidemiological surveillance.